Banality, Memory and the Index: Thomas Demand and Hitler's photographer: Thomas Demand and Hitler's photographer. (1st September 2016) - Brett, Donna West
Abstract : In "The Ontology of the Photographic Image", André Bazin elucidates how photographic images enable the subject to elude death because by its very nature the image preserves the subject through the act of memory and remembering. This characteristic implies an indexical relation between the image and its referent and a reliance on memory's capacity to recall such images. Problematising this position are photographs that are removed from their original context, detached from collective memory and forgotten, or images that, in their very banality, erase or negate meaning? This paper explores the disruption to photography's meaning and memory in selected photographs by Thomas Demand that are restagings of photographs by Adolf Hitler's official photographer Heinrich Hoffmann. This paper analyses these photographs in terms of memory and indexicality and considers how banality can affect the circumstances of looking — a concept that is here applied in order to reconsider these images.